Measuring the Alignment between States’ Finance and Accountability Policies: The Opportunity Gap - Della Sala, Matthew R.; Knoeppel, Robert C. (Education Policy Analysis Archives, 2015)
The research described in this paper expands on attempts to conceptualize, measure, and evaluate the degree to which states have aligned their finance systems with their respective accountability policies. State education finance and accountability policies serve as levers to provide equal educational opportunities for all students – scholars have called for the alignment of education finance and accountability policies as a means for states to meet the demands of educational adequacy. A metric titled the “opportunity gap” was developed, calculated, and tested to represent the degree of misalignment between the equity of states’ finance systems and the intended equity of student performance outcomes defined in accountability policies. School finance and student performance data from nine states were collected for this analysis. Findings indicated that none of the states were delivering simultaneous equity in finance and accountability systems – none of the states provided both equity of finance inputs and equity of student performance outputs. Implications for future research on measuring the alignment between finance and accountability policies are provided by the authors.